2012
DOI: 10.1007/s12199-012-0287-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of socio-economic status and physical health on the long-term care needs of Japanese urban elderly: a chronological study

Abstract: ObjectivesThe aim of this chronological study was to elucidate the effects of socio-economic status (SES) and physical health on the long-term care (LTC) needs of a Japanese elderly population and to explore their causal relationships.MethodsA self-administered questionnaire was distributed to all residents aged 65 years and older of Tama City, Tokyo, in September 2001. A total of 13,195 completed questionnaires were returned, giving a response rate of 80.2 %. A follow-up study was done using the same question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 13 publications
2
11
0
Order By: Relevance
“…Physical health was found to be negatively related to NLTC in this study. This is similar to the research carried out among Japanese elderly [6] and Korean elderly [14], which also found a negative association between physical health and NLTC. Meanwhile, previous researches conducted in the United States of America [8,57] and the United Kingdom [9] also found that having comorbid physical health problems (number of chronic diseases, pain/discomfort) was associated with a higher probability of NLTC.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Physical health was found to be negatively related to NLTC in this study. This is similar to the research carried out among Japanese elderly [6] and Korean elderly [14], which also found a negative association between physical health and NLTC. Meanwhile, previous researches conducted in the United States of America [8,57] and the United Kingdom [9] also found that having comorbid physical health problems (number of chronic diseases, pain/discomfort) was associated with a higher probability of NLTC.…”
Section: Discussionsupporting
confidence: 91%
“…Specifically, lower SES is generally associated with worse physical health outcomes, such as higher rates of long-term mortality among stroke survivors [28], low WHOQOL scores [22], and a lower likelihood of improving functional ability among those with severe disabilities [59]. Our study was identical to one study among the Japanese elderly which also found a positive association between SES and physical health [6]. As for the gender difference, the result of our study is same as a previous study which found that the effect of SES on physical health was similar among the elderly men and women [25], but slightly higher among the elderly women.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The ageing population presents a challenge to health and social care systems, and there will be an enormous increase in health and social service use and expenditure in the near future that requires improvements in how care is organized. Functional limitations, chronic conditions and dementia become more frequent with increasing age, and make people more dependent on other people and services [ 1 , 4 , 5 ]. The ability to cope with the basic activities of daily living (ADL) and the instrumental activities of daily living (IADL) declines with increasing age, and is a common problem in people over the age of 85 [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the use of institutional longterm care (LTC) increases with ageing (Tomiak et al 2000;Luppa et al 2010). Important LTC use predictors often associated with old age are decline in physical and cognitive functioning, (Gaugler et al 2007;Nihtilä and Martikainen 2008;Luppa et al 2010;Yang et al 2013) as well as living alone (Breeze et al 1999;Nihtilä and Martikainen 2008). Having close relatives or having informal care is also associated with the use of LTC; however, the direction of the associations varies (Grundy and Jitlal 2007;Pot et al 2009).…”
Section: Introductionmentioning
confidence: 99%